(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The research results on traction resistance of tractor train consisting of Belarus 80.1 tractor and 2PTS-4-793 trailers, depending on number of trailers, the weight of cargo loaded on them, and speed of movement are specified in the article.